Inquiry-based student worksheets to support numeracy skills - Bhoke, Wilibaldus (Al-Jabar: Jurnal Pendidikan Matematika, 2024)
Background: This study was motivated by the difficulties students face in understanding the concepts taught in the topics of Integers and Decimals.Aim: The research aimed to determine the impact on students' numeracy skills after utilizing Student Worksheets (SW) with an Inquiry-Based Learning Model in Grade V at SDI Lengkosambi.Method: A quasi-experimental design with pre-test and post-test was employed. Data were collected through numeracy tests conducted before and after the implementation of the SW.Results: The findings revealed a significant improvement in students' numeracy skills. The average numeracy score increased from 60% before using the SW to 80% after its implementation. Additionally, the numeracy test scores showed an increase from 42% in the initial AKM Numeracy test to 50% in the final AKM Numeracy test.Conclusion: The use of SW with an Inquiry-Based Learning Model effectively enhanced students' numeracy skills. This improvement indicates that students became more enthusiastic about learning and were better able to solve numeracy-related problems.